Examining the Relationship Among Basic Psychological Needs Satisfaction, Self-Efficacy, and English Achievement of Vocational High School Students in Emergency Remote Teaching - Annisa Annisa; I Gusti Ngurah Darmawan; Dyah Sunggingwaty; Noor Rachmawaty (Borneo Educational Journal (Borju), 2023)
In the context of Emergency Remote Teaching (ERT), this study is conducted to investigate how learning from home impacts Vocational High School students and how their success in English is linked to their well-being, particularly their satisfaction with fundamental psychological needs. To ensure the robustness of the study, questionnaires assessing Basic Psychological Needs Satisfaction, Self-efficacy, and socio-economic factors underwent validation through AMOS software. Notable differences in achievement across eight majors were examined using a one-way ANOVA. The connections among socio-economic factors (such as gender, parental background, and gadget availability), Basic Psychological Needs Satisfaction, Self-efficacy, and students' achievement were delved into through Structural Equation Modeling (SEM). The findings reveal that all student factors, with the exception of Self-efficacy, exerted a significant impact on achievement. It is noteworthy that Self-efficacy exhibited a negative impact, while the presence of gadget availability had the most pronounced positive effect. Interconnections among all these factors were also observed. In summary, the study highlights the influence of various factors, such as socio-economic background and psychological well-being, on the English achievement of Vocational High School students during ERT in Balikpapan, East Kalimantan, Indonesia. The encouragement of students to focus on their well-being, consideration of their family background, and ensuring access to gadgets are deemed critical for achieving better English scores. Future studies can delve deeper using qualitative data and different analysis methods. The inclusion of perspectives from teachers, principals, or parents, coupled with the utilization of standardized English tests, could provide a more comprehensive understanding.